Knowledge Sharing Behavior of Accountants: The Case of Accounting Service Firms in Hanoi - Thi Quynh Anh Doan; Thi Hanh Duyen Nguyen; Duc Tai Do (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
The main objective of this study was to identify, evaluate, and to measure the attributes of knowledge sharing behavior of accountants in the accounting service firms in Hanoi. The study was based on a field survey using a semi-structured questionnaire on a sample of 150 accountants. But, only 120 filled questionnaires were satisfactory and therefore included in the analysis. By using several statistical analytical tools, i.e. descriptive statistics, Cronbach’s Alpha analysis, Independent T-test and ANOVA, the study has identified and measured seven (7) attributes of knowledge sharing behavior that have great effects on employees (or in this case study, accountants). Based on the findings, some recommendations are given for accountants and accounting service firms to improve the knowledge sharing behavior of accountants.